Spin orientation and magnetostriction of Tb1−xDyxFe2 from first principles - Patrick, CE; Marchant, GA; Staunton, JB (American Physical Society, 2020)
The optimal amount of dysprosium in the highly magnetostrictive rare-earth compounds Tb1−xDyxFe2 for room-temperature applications has long been known to be x = 0.73 (Terfenol-D). Here, we derive this value from first principles by calculating the easy magnetization direction and magnetostriction as a function of composition and temperature. We use crystal-field coefficients obtained within density-functional theory to construct phenomenological anisotropy and magnetoelastic constants. The temperature dependence of these constants is obtained from disordered-local-moment calculations of the rare-earth magnetic order parameter. Our calculations find the critical Dy concentration required to switch the magnetization direction at room temperature to be xc = 0.78, with magnetostrictions λ111 = 2700 and λ100 = −430 ppm, close to the Terfenol-D values.